'Becoming citizens': young people making sense of citizenship on a South African community radio station youth show - Karamagi, Sharon Benna Kyakyo (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2012)
This research set out to investigate the role that community radio can potentially play as a space in which young people engage with their own role as citizens and, in so doing, participate in discussions that seek to address social problems in a community divided by class, income, gender and race. The study examines how a local community radio station - Radio Grahamstown - developed a youth programme Y4Yin which the producers of the show and its audience came together to negotiate the meaning of citizenship. The study examines whether this interactive programme was able to function as something like a public sphere where in young people were able to develop a greater sense of agency, at least in the realm of citizenship. Using evidence gathered through focus group discussions with a group of young school-going leamers, interviews conducted with the producers of the show Y4Y, and drawing on Dahlgren's elaboration of a functional public sphere, the research concludes that the show provided a useful platform for Grahamstown high school students to develop their own notions of citizenship and to, at least partially and tentatively, build some 'bridges' across the vectors of socio-economic division in the town. However, the research also concludes that the Y4Y producers often failed to use a mode of address contemporary to the youth and often did not use production techniques congruent with young people's cultural tastes. This limited the programme's appeal and its potential as an enabler of discussion about notions of citizenship and as a platform for social bridging. In addition, because of the producers' control over the choice of topics put up for discussion, open interaction was more limited than could have been expected. In addition, the study also concludes that various limitations to the leamers' freedom of expression (including their fear that teachers might be listening in to the shows) inhibited the programme's role as a deliberative public sphere where issues could be aired, common ground found, and solutions discussed.
Keywords: Citizenship -- Study and teaching -- South Africa; Youth -- Social conditions; Community radio -- South Africa -- Grahamstown; Grahamstown (South Africa) -- Economic conditions